QUEEN OF HERBS‘ELIXIR OF LIFE‟FROM TRADITIONALTO MODERN MEDICINEA TULSI (OCIMUM) (International Journal of Food and Nutritional Sciences, 2022)
Plants are most important natural source of medicine. Worldwide demand of essential oils has increased during the past few years. Essential oils are reported in aromatic plants which are distributed inMediterranean and tropical countries across the world where they are imperative component of the native medicinal systems. Almost all plant organs (flowers, buds, stems, leaves, fruits, seeds and roots) of aromatic plants contain essential oils. Whole plant has been used as traditional medicine for household remedy against various human activities. These are accumulated in secretary cells, cavities, channels, and epidermic cells. Lamiaceaeherb family includes one of the richest essential oil bearing plant family, consists of more than 252 genera and 7000 species of plant Kingdom Lamiaceae family is known for the wealth of species with medicinal properties.